The Value of Pangadereng as A Model For Lecturer Performance Development - A, Arisal; Widyawati, Widyawati; Dwiyama, Fajri (Universitas Pesantren Kh Abdul Chalim Mojokerto, 2024)
Changes in internal dynamics require managing resources effectively, efficiently, and accountably. The research objectives were to find: 1) Description of needs. 2) Prototype Design. 3) Validity and practicality. 4) The effectiveness of the development model for lecturer performance in education and teaching is based on Pangadereng Values ​​at IAIN Bone, which was developed. This research refers to the Borg & Gall model. This research is Research and Development. Data collection: interviews, questionnaires, focus group discussion, feasibility assessment sheets, practicality, product effectiveness. The data obtained were analyzed using descriptive narrative and inferential statistics. The results of the study: a model for developing Lecturer Performance in the Field of Education and Teaching Based on Pangadereng Values ​​at IAIN Bone is needed to improve lecturer performance. The product expert test results show a very valid assessment, and the target user test results are very practical. The results of the effectiveness test showed that the Lecturer Performance Development Model in the Field of Education and Teaching Based on Pangadereng Values ​​at IAIN Bone was effectively used by lecturers to improve lecturer performance at IAIN Bone.